Safety and Hospital Costs Averted Using a Rapid Outpatient Management Strategy for Transient Ischemic Attack and Minor Strokes: The RAVEN Clinic. (April 2021) - Shapiro, Steven D.; Boehme, Amelia K.; Chang, Bernard P.; Miller, Eliza C.; Willey, Joshua; Elkind, Mitchell S. V.
Study Objective: Patients presenting to emergency departments (ED) with transient ischemic attack and minor strokes (TIAMS) are often admitted for evaluation, though experience in other countries have suggested that an expedited outpatient care models may be a safe alternative. We hypothesized that a rapid access clinic for select TIAMS was feasible and would avert hospitalization costs. Methods: This retrospective analysis included patients presenting to our institution's ED with TIAMS and NIHSS ≤5 in calendar year 2017. We referred low-risk patients with TIAMS to a Rapid Access Vascular Evaluation-Neurology (RAVEN) clinic within 24 hours of ED discharge. We identified admitted patients who met RAVEN criteria at ED presentation. Rates of follow-up to the RAVEN clinic were recorded. Financial data collected included total hospital costs and time spent in the ED, as well hospital length of stay for admitted patients with low-risk TIAMS. Results: In 2017, 149 patients were referred to RAVEN clinic and 50 patients were admitted. Of the RAVEN patients 99 (94%) appeared as scheduled. None had clinical changes between ED discharge and clinical evaluation. One patient required hospitalization at the RAVEN evaluation. When compared to RAVEN patients, admitted patients had significantly higher $7, 719 (SD 354) total hospital costs and were hospitalized for 2 days on average. Overall, the RAVEN strategy averted approximately $764, 000 in hospitalization costs and 208 hospital bed-days in accounting year 2017. Conclusions: For select patients presenting with TIAMS without disabling deficits, a rapid outpatient evaluation may be feasible while averting significant total hospital costs and preserving inpatient hospital beds.